‘They stood their ground!’ – Professional Gangsters in South African Indian Society, 1940 - 1970 - Heatlie, Damon (My University, 2019)
This thesis is one part of a Creative PhD that investigates the emergence of a new breed of South African Indian gangsters in Durban and Johannesburg in the early apartheid period. The second part, existing as a separate creative text, is a screenplay for a feature film loosely based on dynamics and events present in the Durban Indian underworld of the 1950s. In the thesis I argue that while prominent ‘professional’ Indian gangsters were similar to other ‘non-white’ gangsters in certain respects (their self-fashioning in relation to gangster films, for one), these ‘gentlemen gangsters’ were different in terms of their high level of social and economic integration into Indian society. Focusing on the Crimson League in Durban and Sherief Khan’s gang in Johannesburg, this research comprises reconstructions from (and analysis of) interviews and written sources. It shows how these hustlers positioned themselves as protectors of the Indian community, but also cultivated reputations as punishers, capable of brutal violence if opposed. In Chapter 1, I explore the world of changing South African Indian identity in the middle decades of the twentieth century, and the mobilisation of an ‘Indian’ identity by disparate groups to advance collective interests. In Chapter 2, I look at how subjugated Indian masculinity, a sense of vulnerable ‘territory’, and the rise of street gangs intersected in ritualised games of soccer and gang fights. Chapter 3 traces the rise of Durban’s dominant gang in the early apartheid period, the Crimson League, a vigilante outfit that turned to illicit activities and thuggery. Chapter 4 looks at some of the adversaries that the League engaged and ultimately defeated, including the Salots and the Michael John Gang – I dissect the John murder trial to show how the Crimson League seemingly bent the law to their will. In Chapter 5, I move on to a description of Sherief Khan’s rise to power over rival Old Man Kajee in the Indian areas of Johannesburg in the 1940s and early1950s, culminating in an analysis of his gang’s various ‘business’ activities. Chapter 6 finds Khan and company back on the streets in the 1960s - and examines a decisive conflict with contenders, the ‘Malay Mob’, that re- established Khan’s reputation as ‘South African king of the underworld’. In Chapter 7, I look at how mid-century Hollywood gangster films resonated with Indian gangsters, and how a convoluted conversation between Drum magazine, Hollywood films and Indian gangsters developed. Chapter 8 concludes the analysis with considering the thriving South African Indian cinema scene of this period, and how the cinemas functioned as multifaceted fantasy spaces for both gangsters and ordinary Indians.
A thesis submitted in partial fulfilment of the requirements of the degree of Doctor of Philosophy by creative project and dissertation to the Faculty of Humanities, Wits School of Arts, University of the Witwatersrand, Johannesburg, 2019.
Keywords: South African Indian gangsters; Crimson League in Durban; Sherief Khan’s gang in Johannesburg; South Africa; South African Films; Ritualised games of soccer and gang fights; South African Indian cinema scene; Cinematography; UCTD